A Social Constructivist Approach to Management of Primary Student Behavior - Hang, Ngo Vu Thu (VNU Journal of Science: Education Research; Vol 37 No 2, 2021)
To teach lessons effectively, primary teachers need to effectively manage student behavior. Good student behavior management helps teachers receive a smooth coordination from students in classroom practices. This article provides knowledge base for primary teachers in managing student behavior and presents some possible measures to help primary teachers effectively manage student behavior. The article focuses on clarifying the issues of characteristic of primary students, principles of student behavior management, and measures of effective behavior management. The article applies a student-centered approach and social constructivism to provide measures to manage student behavior. The article not only works for primary teachers but also has many meanings for educational administrators and trainers in order to improving the implementation of General Education Program of 2018 in the current context of educational innovation.